2017
DOI: 10.1021/acs.jafc.7b04134
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpenoid Saponins from Green Vegetable Soya Beans and Their Anti-Inflammatory Activities

Abstract: Ten compounds were isolated and identified from green vegetable soya beans, of which five are new triterpenoid saponins (1-5) and five are known compounds (6-10). The chemical structures of the five triterpenoid saponins (1-5) were elucidated to be 3β,24-dihydroxy-22β,30-epoxy-30-oxoolean-12-en 3-O-α-l-rhamnopyranosyl-(1 → 2)-β-d-xylopyranosyl-(1 → 2)-β-d-glucuronopyranoside, 1; 3β,24-dihydroxy-22β,30-epoxy-30-oxoolean-12-en 3-O-α-l-rhamnopyranosyl-(1 → 2)-β-d-(3″-O-formyl)-galactopyranosyl-(1 → 2)-β-d-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…First, results from this study further support the in vivo anti-inflammatory bioactivities of soyasaponins. In recent years, many studies have demonstrated that soyasaponins exhibit anti-inflammatory bioactivities by reducing the pro-inflammatory cytokines and/or mediators (TNFа, IL- [7][8][9][10][11][12][13][14][16][17][18][19]. However, only a few of investigations provided in vivo evidences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, results from this study further support the in vivo anti-inflammatory bioactivities of soyasaponins. In recent years, many studies have demonstrated that soyasaponins exhibit anti-inflammatory bioactivities by reducing the pro-inflammatory cytokines and/or mediators (TNFа, IL- [7][8][9][10][11][12][13][14][16][17][18][19]. However, only a few of investigations provided in vivo evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Kinjo et al (2000) reported that soyasaponin III had antiinflammatory properties by exhibiting in vitro anticomplementary activity [15]. More recently, Lan et al isolated and identified five new triterpenoid saponins from green vegetable soya beans and found that three of them exhibited moderate anti-inflammatory activities by inhibiting the release of NO in LPS-stimulated RAW264.7 cells [16]. We recently found that soyasaponins (A 1 , A 2 or I) inhibited inflammation (reduced PGE 2 production and COX-2 expression) by suppressing the reactive oxygen species (ROS)-mediated activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/ NF-κB signaling pathway [17].…”
Section: Introductionmentioning
confidence: 99%
“…Triterpenoids are highly diverse natural products widely distributed in plants with various biological activities. , For instance, glycyrrhizin, a triterpenoid extracted from licorice, is applied as medicine and a natural sweetener due to its various pharmacological effects and strong sweetness . β-Amyrin is also a kind of triterpenoid with similar pharmacological activities as glycyrrhizin and serves as a key precursor to a wide range of triterpenoid products .…”
Section: Introductionmentioning
confidence: 99%
“…Their anti-inflammatory activities were investigated by the Griess reagent. Generally, nitric oxide (NO) modulates important cellular signaling pathways involved in immunity and inflammation, and nitric oxide synthases (NOSs) play a substantial role in producing NO. , The Griess reagent was employed for the determination of nitrite, the reaction product of NO with O 2 , to quantitate NO production. , On the basis of the successful inflammatory model, all isolated compounds from cumin seeds were employed to detect their inhibitory effect on the nitrite level using LPS-stimulated RAW264.7 macrophage cells. As shown in Figure A, the majority of the compounds displayed significant inhibitory influence on the nitrite level.…”
Section: Resultsmentioning
confidence: 99%